Enhancing The Eighth Grade Students' Vocabulary Achievement By Using Pelmanism Game At SMPN 5 Jember - Pratiwi, Bella; Ariani, Musli; Ariyanto , Sugeng (English Education Study Program, 2016)
This classroom action research was intended to enhance the eighth grade students’ vocabulary achievement at SMPN 5 Jember by using pelmanism game. Purposive method was used to choose the research area and the research subject. The primary data were collected by using observation and vocabulary test. The supporting data were collected by interview and documentation. Both the results of observation and the vocabulary test were analyzed statistically by using percentage formula. The students’ participation in Cycle 1 was 58.5% and in Cycle 2 was 77%. Meanwhile, the result of students’ vocabulary achievement in Cycle 1 was 75% and in Cycle 2 was 80%. It means that the use of pelmanism game could enhance the students’ vocabulary achievement. Therefore, it is suggested to use pelmanism game to enhance the students’ vocabulary achievement.